Хроника Иркутской организации Союза архитекторов СССР – РФ - Antipin, Lyutsian; Grigoryeva, Elena; Lyapin, Andrei (проект байкал, 2015)
The Irkutsk Organization of the Union of Architects is 80. Our journal has published many articles and special issues about foundation, different life stages and prominent architects of the organization. As it is known, the Russian history of voluntary creative unions of registered architects and specialists takes origin from the Moscow Architectural Society with the Charter of 27 October 1876. Then followed the Saint Petersburg Society of Architects, and later on creative unions of architects, artists and civil engineers were established in different cities. In the XIXth century the present Union was initiated by such eminent masters as M. D. Bykovsky and F. O. Shekhtel followed by K. S. Alabyan and many other celebrities. The unions of architects have made a considerable contribution to research and development of architectural design and construction, and to cultural heritage protection. Numerous competitions were of particular importance. Their results are buildings that have gone down in history of architecture of the XXth century.